PEMANFAATAN MEDIA SOSIAL INSTAGRAM SEBAGAI SARANA PEMASARAN PRODUK TOUR AND TRAVEL DI DESA PINGE - Made Ayu Juliantini, Ni; Rizky Mahendra, I Putu; Griselda Pangaribuan, Tasya; Made Riko Hendrajana, I Gusti; Lanovia Amir, Firlie (Penerbit Lafadz Jaya, 2023)
The tourism industry is one of the largest industries in the world, including Indonesia. So, it is said that this industry has considerable influence, so that it becomes an opportunity for business. Pinge Village is a small tourist village that is old enough to offer various tourist attractions jogging trekking, picking flowers, and planting rice. In addition, there are beautiful views, and a cool and beautiful atmosphere. This study aims to determine the influence of Instagram social media promotions on the decisions of tourists visiting Pinge Village. The method used in this research is qualitative method. The qualitative method is a method that observes directly, and this method produces a more comprehensive study of a phenomenon. The results of the study show that there is still a lack of marketing strategy through Instagram social media, a lack of the community's role in developing tour packages.